2016
DOI: 10.1007/s13224-016-0928-5
|View full text |Cite
|
Sign up to set email alerts
|

A New Dawn for Intrauterine Insemination: Efficient and Prudent Practice will Benefit Patients, the Fertility Industry and the Healthcare Bodies

Abstract: This review addresses the misplaced facts about the IUI procedure within a lucrative fertility industry. Evidence suggests IUI must be a first-line treatment option for most couples except in cases of bilateral tubal blockage and severe oligozoospermia. We introduce the concept of using 'consecutive ejaculation' in men with subfertility and one which can radically alter the male infertility definition, thereby providing a new approach to examining and managing male factor infertility. The review also explores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In the present study, there was a higher CPR in the bi-follicular growth compared with the mono-follicular growth, and we also performed a comparative analysis to detect the effectiveness of rFSH and CC in mono-and bi-follicular developments separately. Bahadur et al (2017) also concluded that pregnancy rates may be improved in IUI cycles using gonadotrophin with 2 preovulatory follicles compared to CC cycles. In another opinion article, Bahadur & Homburg (2019) suggested that the evidence about IUI should be updated.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was a higher CPR in the bi-follicular growth compared with the mono-follicular growth, and we also performed a comparative analysis to detect the effectiveness of rFSH and CC in mono-and bi-follicular developments separately. Bahadur et al (2017) also concluded that pregnancy rates may be improved in IUI cycles using gonadotrophin with 2 preovulatory follicles compared to CC cycles. In another opinion article, Bahadur & Homburg (2019) suggested that the evidence about IUI should be updated.…”
Section: Discussionmentioning
confidence: 99%
“…This observation shows the potential benefit of SRI. IUI is a cost-effective method for increasing pregnancy rates in couples with unexplained infertility, which is why IUI is often chosen as first-line therapy in these patients 32 . One could speculate that an improvement in success rates with SRI might further reduce the number of referrals for more expensive assisted reproductive technology, and hence reduce the overall costs of infertility treatment; however, carefully designed clinical trials would be required to prove this.…”
Section: Discussionmentioning
confidence: 99%
“…It is a simpler and less intrusive procedure than other ART methods, is widely available, and can be a successful and safe option in selected patients. 21 Studies suggest that oral NMP and NMP-SR may be an effective and feasible option in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…IUI can be associated with pregnancy rates of 10-20% per cycle. 21 Use of oral NMP in the IUI setting has been evaluated largely in observational studies (Table 1 ). A prospective observational analysis of 591 IUI cycles in which a single follicle was developed found that the clinical pregnancy rate was improved with oral NMP compared with no luteal support.…”
Section: Intrauterine Inseminationmentioning
confidence: 99%